A formação da Cooperativa Habitacional Beltronense: implantação e ocupação dos loteamentos cooperados no município de Francisco Beltrão - Quaglioto, Wlademir Carlos (2018)
The option to work with Cooperative Housing Beltronense - Coohabel comes as it completes 10 years of its installation in the Municipality of Francisco Beltrão-PR. The dissertation seeks to highlight aspects of the creation, installation and favoring or not of the existence of the housing cooperative to its members. Several bibliographic and documentary sources were used, among them are: data from the Municipality of Francisco Beltrão on land subdivisions, data from Coohabel, Law n. 5,764, of December 16, 1971, which defines the National Cooperative Policy and establishes the legal regime of cooperative societies with guidelines and measures for their better development and responses to their members. Statute of the cities Law nº 10.257, of July 10, 2001, which regulates articles 182 and 183 of the Federal Constitution that establish general directives of the urban policy and gives other measures, Master Plan of the Municipality of Francisco Beltrão and its alterations. The municipality of Francisco Beltrão faces the same difficulties of most Brazilian cities, with a development of the urban perimeter unrelated to planning, causing difficulties for the population in the search for housing. With an unplanned urban occupation, the problems impact the city as a whole, where the organized and concentrated housing market excludes many families to the outskirts of the city or excludes the right to the city, leaving a portion of the population without access to a decent dwelling. Forcing a certain layer of the population to organize to face this market that makes difficult the search for housing to a portion of the population of the municipality. Faced with this problem, the dissertation had the objective of understanding the process of formation of the Cooperative housing in Francisco Beltrão - Coohabel. Analyzing the search for a portion of the population of the municipality by a cooperative association of housing to have the possibility of acquiring land for the construction of their dwelling. The use and occupation of the urban land in the Municipality of Francisco Beltrão, as well as the legal aspects, the characterization of the municipality, origin of the population involved in the process of the formation and structuring of the housing cooperative were observed.